Taking spoofs seriously: Spoofs as counter-narratives in volunteer discourse - Maagaard, Cindie; Lundholt, Marianne Wolff (MedieKultur: Journal of media and communication research, 2018)
This article explores how the theoretical framework of “counter-narrative” can be a resource for the analysis of spoofing videos. Using spoofs deployed by activist organizations to critique Western aid appeals and “voluntourism,” we 1) investigate the intertextual mechanisms of spoof videos as counter-narrative and how spoofers borrow generic conventions and use them to create alternative narratives, and 2) discuss the consequences of their cultural depictions, for example, for the discourse of volunteering, which we examine here, particularly in light of tendencies toward self-reflecting campaigns identified by Chouliaraki (2013). Through these understandings, we draw lessons about the counter-narrative potential of spoofs used as critique and edification and their ambivalent status as counter-narratives. As critiques, they may hold a mirror to viewers’ self-perceptions and motivations. Yet, this self-reflexive strategy carries the risk of self-congratulatory complicity with the genres they seek to critique and the discourses and power relations upon which they depend